A multilevel N log N algorithm for solving boundary integral equation - Weng Cho Chew; Cai-Cheng Lu (IEEE Antennas and Propagation International Symposium, 1994, 1994)
Multilevel algorithms have been used to generate fast algorithms for Fourier transforms and inversion of matrices in finite element method. They usually involve nesting a smaller problem within a larger problem. Recently, multilevel algorithms have been used to solve integral equation by expediting matrix-vector multiplies or by finding the inverse of the integral operator. Interpolation multilevel algorithm has also been proposed. These algorithms could invert an integral operator in less than O(N/sup 3/) operations and expedite a matrix-vector multiply to require O(Nlog N) or O(N) operations. In this paper, we will describe a multilevel algorithm for expediting matrix-vector multiply in an iterative solution of boundary integral equation. The algorithm has O(N(log N)/sup 2/) complexity, and for very large problem, O(Nlog N) complexity.< >